Poor Outcome of Above-Knee Amputation after Septic Failure of Revision Total Knee Arthroplasty - Böhle, Sabrina; Rohe, Sebastian; Kirschberg, Julia; Brinkmann, Olaf; Seeger, Jörn; Zippelius, Timo; Matziolis, Georg; Röhner, Eric (The Journal of Knee Surgery, 2020)
Persistent periprosthetic infection following total knee arthroplasty is one of the most dreaded complications of orthopaedic surgery. Treatment strategies include arthrodesis of the knee joint, stable fistula, long-lasting antibiotic therapy, or above-knee amputation. The advantage of amputation in comparison to other treatment options is the possible cure of infection, because the source of infection is removed and no foreign material left in situ. The aim of the study is to examine whether a septic amputation of the femur in case of persistent periprosthetic infection at the knee joint leads to the healing of the patient. Moreover, the physical and mental state should be evaluated. All patients with above-knee amputation because of periprosthetic joint infection after primary total knee arthroplasty between 2016 and 2018 were included in this retrospective study. A questionnaire with the clinical scores visual analog scale, modified Lysholm, Western Ontario and McMaster Universities Osteoarthritis Index and 36-Item Short Form Survey has been designed. In addition, all characteristics and perioperative data were documented. Eleven patients were included in the study. One patient died after above-knee amputation; all other patients live with a marked impairment of quality of life but with absence of the infection of the leg. Two out of ten are able to walk regularly with an exoprosthesis with forearm crutches, 50% are in a wheelchair, while 30% are bedridden. Patients with above-knee amputation after persistent periprosthetic infections were free of infection and without signs of inflammation. However, this is associated with worse mobility and high mortality rate.
Keywords: periprosthetic joint infection; total knee arthroplasty; lower limb amputation; knee arthrodesis